SOCIAL AND ECONOMIC ESSENCE OF COMPULSORY INSURANCE - Hamrayeva F. Sh (PT. Antis International Publisher, 2024)
Through the mandatory insurance system, the state participates in solving social problems of society's development. The importance and nature of compulsory insurance is revealed in the article.